Sustainable Education and Student Action: Understanding Student Contributions to Addressing Climate Change - Fritz Hotman Syahmahita Damanik; Saliman Saliman (Postgraduate, University of Mataram, 2023)
This study aimed to identify new factors in sustainable education that are able to motivate students for action related to climate change, and to evaluate the influence of the student movement for climate change on student actions. This research was conducted through a literature review research method. This research provides an explanation of existing findings and data. The results show that formal education in schools and social activities, such as interactions between students, can form a culture that supports sustainable collective action. An evaluation of the student movement in climate change mitigation, including activities such as recycling and waste collection, provides insight into its positive impact. This research contributes to designing educational approaches that motivate and evaluate student action on climate.